2015
DOI: 10.1016/j.jjcc.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low level of high-density lipoprotein-cholesterol sampled in overnight fasting state on the clinical outcomes in patients with acute myocardial infarction (difference between ST-segment and non-ST-segment-elevation myocardial infarction)

Abstract: Low HDL was associated with significantly higher risk of in-hospital mortality in STEMI patients, but not in NSTEMI patients. Thus, more aggressive treatment should be considered in STEMI patients with low HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…20 The previous KAMIR study results supported the strategy of reducing of LDL-cholesterol ≥50% from baseline. 17, 21 Recently, the Improved Reduction of Outcomes: Vytorin Efficacy International Trial (IMRPOVE-IT) study proposed that lower is better, and the role of non-statin lipid-lowering agents for improving cardiovascular outcomes. 22 In this clinical setting, the newer KAMIR-NIH registry will investigate the target of LDL-cholesterol and the effect of nonstatin agents in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…20 The previous KAMIR study results supported the strategy of reducing of LDL-cholesterol ≥50% from baseline. 17, 21 Recently, the Improved Reduction of Outcomes: Vytorin Efficacy International Trial (IMRPOVE-IT) study proposed that lower is better, and the role of non-statin lipid-lowering agents for improving cardiovascular outcomes. 22 In this clinical setting, the newer KAMIR-NIH registry will investigate the target of LDL-cholesterol and the effect of nonstatin agents in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Angeloni et al showed similar 3-year MACE rates in low and high HDL-C groups, even in patients who underwent coronary artery bypass grafting [24]. Ji et al also showed no significant difference in 1-year MACE rates between the two groups in AMI patients [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the studies using the cut-off value of 40 mg/dL suggested that low HDL-C was an independent risk predictor [1214]. Other studies using different cut-off values for men and women (40 mg/dL for men and 50 mg/dL for women) failed to show the significance of low HDL-C [2325]. More importantly, 2 studies from the same AMI registry showed different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these individuals, the benefit of LDL-C lowering with statin therapy does not correlate with the reduction of cardiovascular event rates [4]. Other studies found a strong association between low HDL-C, high triglyceride (TG) levels, and cardiovascular risk [5][6][7] even in patients on statin therapy [2]. Elevated levels of original article TG-rich lipoproteins have inflammatory, thrombotic, and atherogenic effects whereas HDL particles are generally considered to be anti-atherogenic owing to their participation in the reverse cholesterol transport and antioxidant and anti-inflammatory defense mechanisms [8].…”
Section: Introductionmentioning
confidence: 99%